Manifestations of paediatric Leishmania infantum infections in Malta. - Pace, D; Williams, T; Grochowska, A; Betts, A; Attard-Montalto, S; Boffa, M; Vella, C (2011)
Leishmania infantum is endemic in the Maltese archipelago, a group of islands in the Mediterranean which are visited frequently by tourists from Northern European countries. The burden of leishmaniasis is highest in children who may present with cutaneous or visceral manifestations. We describe systematically the manifestations, diagnosis and management of leishmaniasis in children <14 years of age, who had a histopathological diagnosis of leishmaniasis in Malta, from 2004 to 2008. Eleven children were diagnosed with leishmaniasis; 8 children (15-44 months of age) had visceral disease and three (aged 9-13 years) suffered cutaneous infections. Prolonged high grade fever, pallor, hepatosplenomegaly, and pancytopenia were common presenting features of visceralisation. Diagnosis was based on the visualisation of amastigotes from bone marrow aspirates. Pentavalent antimonials were associated with treatment failure in two children, whilst liposomal amphotericin B was curative in all. Children with cutaneous leishmaniasis had dry crusted ulcero-nodular lesions on exposed areas which responded to intra-lesional instillation of sodium stibogluconate or to cryotherapy. Leishmaniasis should be included in the differential diagnosis of fever and hepatosplenomegaly or chronic cutaneous lesions in children who travel to Malta.